Social Impact and Sustainability of Corporate Social Responsibility in the Banking Sectors: Bangladesh Perspective - Mohammad, Niaz; Kamal, Shah (Asian Business Review, 2016)
In the recent years Corporate Social Responsibility (CSR) has witnessed a tremendous increase in awareness and control in the global arena. It is a concept where business organizations apart from their profitability and growth show interest in societal and environmental welfare by taking the responsibility of impact of their activities on stake holders, employees, shareholders, customers, suppliers, and civil society. However, in developing nations the situation of CSR activities of financial institutions is not so flourishing. The aims of this study are to investigate the Corporate Social Responsibility (CSR) activities performed by ten commercial banks in Bangladesh and explore the potential social impacts and sustainability in the future. This study also traced to find the relationship among operational performance by contributing CSR activities. CSR activities affect social attention to the customers and related stakeholders. It shows the relation between after tax net operating income and CSR expenditures by banks using SPSS software.
Keywords: Corporate Social Responsibility; Sustainability; CSR reporting; Performance Measurement